(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, a lot of people use gadgets not just to communicate with loved ones, but also to lessen there boredom, due to the expansion of technology and newly updated gadgets. That’s why people get obsessed with using gadgets, which turns into bad habits; a lot of bad things can be learned by using the internet, especially for those children who have not been properly guided by their parents. In line with the purpose of the study, which is to know the perception of students regarding the impact of the SIM Card Registration Act 11934 on cybercrime, the researchers will use the descriptive research design. The population of the study is the students at Bestlink college of the Philippines; specifically, the respondents comprise 50 students. The major instrument used for gathering data was a survey questionnaire. This study gives the respondents and future researchers additional knowledge about the SIM Card Registration Act. Future researchers can focus on the respondents, such as the delivery riders, to know their perception of the SIM Card Registration Act. Future researchers can focus on studying the SIM Card Registration Act to gain more knowledge and understand this new mandatory registration act 11934. Future researchers could also focus on the advantages and disadvantages of the newly mandatory SIM card Registration Act 11934.